Analysis of The Effect of Capital, Credit Risk, and Liquidity Risk on Profitability in Banks - Antyo Pracoyo; Aulia Imani (Indonesia Banking School, 2018)
This research aims to analyze the influence of bank-specific component to profitability of banking industry within the classification of commercial banking category 3 (Bank Umum Kegiatan Usaha 3, classification based on Central Bank of Indonesia) in the period of 2011 until 2015. The number of sample for this research are 8 banks or Bank Devisa. Independent variable used for this research are based on the ratio of banks. There are Capital measured by Capital Adequacy Ratio, Credit Risk measured by Non Performing Loan, and Liquidity Risk measured by Loan to Deposit Ratio. While dependent variable Profitability measured by Return On Assets. This research analyzed using Eviews 7 program for Panel Data Regression. The result of this research shows that Capital and Liquidity Risk has insignificance effect to Profitability. Meanwhile, Credit Risk has significant effect to Profitability